Prevalence and risk factors for exposure to Toxoplasma gondii in slaughterhouse workers in western Kenya - Cook, Elizabeth A.J.; Gitahi, N.; Glanville, William A. de; Thomas, Lian F.; Kariuki, S.; Kang'ethe, Erastus K.; Fèvre, Eric M. (Springer, 2021)
Background Toxoplasma gondii is a zoonotic protozoan parasite infecting warm-blooded animals. Infection in people can occur through ingestion of oocysts passed in the faeces of the definitive hosts; ingestion of bradyzoites in the tissue of infected intermediate hosts; or exposure to tachyzoites in raw milk and eggs. Slaughterhouse workers are considered a high-risk group for T. gondii exposure because of their contact with raw meat, although a positive relationship between handling raw meat and T. gondii seropositivity has not been demonstrated in all studies. This study aimed to determine the seroprevalence of antibodies to T. gondii in slaughterhouse workers in Kenya and identify risk factors associated with seropositivity. Methods A survey of slaughterhouse workers was conducted in 142 slaughter facilities in the study area. Information regarding demographics, contact with livestock, meat consumption, and practices in the slaughterhouse was collected using structured questionnaires. Commercial ELISAs were used to detect IgM and IgG antibodies against T. gondii and a multi-level logistic regression model was used to identify potential risk factors for seropositivity in slaughterhouse workers. Results The apparent prevalence of antibodies to T. gondii was 84.0% (95% Confidence Interval (CI) 81.2–86.5%) for IgG and 2.2% (95% CI 1.3–3.5%) for IgM antibodies. All IgM positive individuals were IgG positive. Risk factors for exposure to T. gondii were: increasing age (Odds Ratio (OR) 1.03; 95% CI 1.01–1.05); owning poultry (OR 2.00; 95% CI 1.11–3.62); and consuming animal blood (OR 1.92; 95% CI 1.21–3.03). Conclusions The seroprevalence of antibodies to T. gondii was very high in this population and considerably higher than published values in the general population. Risk factors included age, owning poultry and drinking animal blood which were consistent with previous reports but none were specifically associated with working in the slaughterhouse. In this instance slaughterhouse workers may represent a useful sentinel for the general population where the level of exposure is also likely to be high and may signify an unidentified public health risk to vulnerable groups such as pregnant women. A detailed understanding of the epidemiology of infection is required, which should include an assessment of incidence, mortality, and burden since T. gondii infection is likely to have life-long sequelae.